The storytelling of destination podcasts of government tourism agencies for the promotion and construction of territorial identity. - Fitó-Carreras, Maria; Vidal-Mestre, Montserrat; Freire-Sánchez, Alfonso (Radio Journal: International Studies in Broadcast & Audio Media, 2025)
The podcast has emerged as a format for the promotion of tourism destinations. This study explores how, through branding, governmental tourism agencies convey the identity of the territory they represent and manage to create travel expectations among their stakeholders. We therefore employed a descriptive documentary method with a quantitative and qualitative approach and analysed titles produced by fourteen agencies. The results reveal that the most used genre for the construction of the narrative is the interview and the least used is fiction and that local expert sources predominate, with a notable participation of voices recognized by the audience and influencers. We conclude that the sampled destination podcasts meet the needs of future travellers by providing valuable information about the destination through legitimized voices and making the territory's identity known in all its dimensions.